VD_FINDINFO HC / 2018 / 954 vom 24. September 2018 - VD Tribunal cantonal (2018)
JURIDICTION ARBITRALE, MOTIF DE RÉVISION, RÉVISIONDÉCISION, FAUX TÉMOIGNAGE | 73 al. 1 LOJV, 356 CPC (CH), 396 CPC (CH), 397 CPC (CH), 47 CDPJ